An assessment of isometric muscle strength and the hamstring: Quadriceps ratio among males trained with free weights vs. machines - Geferson Honorato Da Silva; Alex Souto MAIOR (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2022)
Introduction. The purpose of this study was to assess the isometric muscle strength (IMS) of the knee extensors and flexors, bilateral asymmetry (BA) and the hamstring: quadriceps ratio (H:Q ratio) between the dominant leg (DL) vs. the non-dominant leg (NDL) of males trained with free-weights vs. machines. Material and Methods: Thirty males were recruited and separated into two groups: Free-weights (n = 15) and Machines (n = 15) groups. All study participants performed the IMS testing for knee extensors and flexors in the DL and NDL using a commercially available load cell. The highest value obtained from the three trials was used for statistical analysis. Results: The IMS of the quadriceps and hamstring muscles for DL and NDL showed a significant increase in the Free-weight group when compared to the Machine group. In addition, a significant difference (p <.03) in the IMS of hamstring muscles between DL vs. NDL was observed in the Machine group. The H:Q ratio on DL (p < .002) and NDL (p < .01) was significantly higher in the Free-weight group. Conclusion: This study showed better isometric muscle strength of the thigh (hamstring and quadriceps) and the H:Q ratio in males trained with free weights. In addition, males trained with machines showed a bilateral asymmetry of the hamstring muscles and a lower H:Q ratio - consequently, a higher risk of knee injuries.